Scientific temperaments : - Hilts, Philip J. (Simon and Schuster, 1982)
Contents: one: The man ring, Robert Wilson and the Building of Fermilab ; two: on divinity avenue, Mark Ptashne and the Revolution in Biology ; Three: Doll inside a Doll, John McCarthy and the Evolution of Artificial Intelligence, ...